A review on the laws of polygamy in federal territories of Malaysia / Izmi Izdiharuddin Che Jamaludin Mahmud - Che Jamaludin Mahmud, Izmi Izdiharuddin (2012)
In Malaysia, the Islamic law is the state subject and administered by Syariah Courts. From various Malaysian legislation of Islamic family law, most of Islamic law in Malaysia followed the Islamic Family Law (Federal Territories) Act 1984 as a model. Section 23 of Islamic Family Law (Federal Territories) Act 1984 is the main basis for the husband to apply for polygamy. However, there are many ambiguities in the application for polygamy such as the protection available to the existing wife and the health condition of first wife as a condition to exercise polygamy. Furthermore, there are defects in the punishment imposed for committing polygamy without permission from the Court under Section 123 of Islamic Family Law (Federal Territories) Act 1984 as the husband is only required to pay penalty in order to legalise and register the polygamy in Malaysia. Thus, in order to strengthen the law of polygamy in Federal Territories, there are few references and recommendations based on Al Quran, Hadith, and various school of fiqh in order to overcome the problems relating the law of polygamy in Federal Territories.